(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This survey research aimed to evaluate the efficiency of Katarungang Pambarangay in resolving domestic disputes in Barangay Kaligayahan, Quezon City. The study utilized a descriptive research method and involved the participation of 50 respondents, including 20 Barangay Personnel and 30 Barangay Residents, selected through purposive sampling. The major instrument for data gathering was a survey questionnaire that employed a percentage formula, ranking, weighted mean, and Likert scale to determine the efficiency of Katarungang Pambarangay. The results of the study showed that the efficiency of Katarungang Pambarangay in resolving domestic disputes at Barangay Kaligayahan, Quezon City, was perceived as "very effective" by the respondents in terms of settlement, enforcing law, and Barangay assistance. However, some problems encountered during the proceedings, such as non-attendance of respondents and complainants, lack of knowledge about their rights, and disobedience of commands by Barangay officials, were also identified. The respondents suggested that the Barangay officials should undergo training and seminars to become more effective in their duties. To address the issues encountered in barangay proceedings, a multi-pronged approach is recommended. Clear communication, follow-up measures, and education about rights and responsibilities should be provided to all parties involved. Providing training and resources for barangay officials and regularly assessing their performance is also important.